Enantioselective Template‐Directed [2+2] Photocycloadditions of Isoquinolones: Scope, Mechanism and Synthetic Applications. Issue 18 (17th March 2015) - Coote, Susannah C.; Pöthig, Alexander; Bach, Thorsten
Abstract A strategy for the enantioselective [2+2] photocycloaddition of isoquinolones with alkenes is presented, in which the formation of a supramolecular complex between a chiral template and the substrate ensures high enantioface differentiation by shielding one face of the substrate. Fifteen different electron‐deficient alkenes and ten different substituted isoquinolones undergo efficient photocycloaddition, yielding the cyclobutane products in excellent yields and with outstanding regio‐, diastereo‐ and enantioselectivities (up to 99 % ee). The mechanism of the reaction is investigated by means of triplet sensitization/quenching and radical clock experiments, the results of which are consistent with the involvement of a triplet excited state and a 1, 4‐biradical intermediate. The variety of functionalized cyclobutanes obtained using this approach can be further increased by straightforward synthetic transformations of the photoadducts, allowing rapid access to libraries of compounds for various applications.